Integrating gender with the water-energy-food-ecosystem nexus in Egypt’s salinity-affected lands - Al-Zu’bi, Maha; Abu-Zeid, M.; El-Atfy, H.; Hassan, M.; Azab, A.; Halim, M.; Gebril, H.; Ihab, S.; Tawfik, Mohamed; Brouziyne, Youssef (International Water Management Institute, 2025)
Egypt’s agricultural sector is increasingly threatened by climate change, water scarcity and soil salinization, especially in the Nile Delta. These challenges disproportionately affect rural women, who form a significant share of the agricultural workforce yet face persistent barriers to land, finance, technology and participation in decision-making. Integrating gender considerations into the Water–Energy–Food–Ecosystem (WEFE) Nexus is essential to designing scalable and context-appropriate climate-resilient solutions. This policy brief synthesizes insights from a 2024 policy roundtable, expert consultations and recent evidence to identify pathways for scaling gender-responsive innovations in salinity-affected landscapes. Case studies from Fayoum, Qena and Kafr El-Sheikh demonstrate how solar-powered irrigation, IoT-enabled water management and salt-tolerant crops can boost productivity, reduce labor burdens and enhance women’s resilience—yet financial, institutional and infrastructural constraints continue to limit broader adoption. The brief outlines priority actions, including strengthening the enabling environment for scaling, directing climate finance to women in high-risk areas, ensuring equitable access to mechanization and climate information, supporting collective action through women’s groups, and fostering farmer-led innovation. Expanding gender-responsive research and leadership opportunities for women and youth is also critical. Centering gender equity within the WEFE Nexus will enable Egypt to enhance climate resilience, improve food security and promote more inclusive and sustainable agricultural development in salinity-affected regions.